Самовар с шампанским: [роман] / Дарья Донцова - Донцова Дарья Аркадьевна (Иронический детектив, 2015)
Экземпляры: (20190418) / Инвентарный номер: 50189 / Цена: 20.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Д 67 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6